A comparative study of performance between TKX-50-based composite explosives and other composite explosives. Issue 2 (3rd April 2019) - Zhou, Meng-nan; Chen, Shu-sen; Wang, Dong-xu; Yu, Yue-hai; Wang, Jian-quan; Li, Jin-xin; Wang, Na; Chen, Ming-lei
ABSTRACT: Dihydroxylammonium 5, 5′-bistetrazole-1, 1′-diolate (TKX-50) is a promising candidate for high-energy explosive (e.g. HMX), which can be used as the main component in composite explosive formulations processed through a melting method. In the present study, TKX-50-based explosive composites were prepared using 2, 4, 6-Trinitrotoluene (TNT) or TNT/wax as the carrier, and were compared with HMX-, 3-nitro-1, 2, 4-triazol-5-one (NTO)-, and hexahydro-1, 3, 5-trinitro-1, 3, 5-s-triazine (RDX)-based formulations. Crystal stability, surface micro-topography, thermal decomposition performance, mechanical property, thermal sensitivity, and mechanical sensitivity of the composites were comprehensively investigated. Overall, TKX-50-based formulations exhibited improved properties with a superior safety performance compared to HMX- and RDX-based formulations and better mechanical properties than NTO-based formulations.